2021
DOI: 10.1109/access.2021.3108232
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stability of p-Channel Feedback Field-Effect Transistors Under Bias Stresses

Abstract: In this study, we examined electrical stability of the p-channel feedback field-effect transistors (FBFETs) under negative bias stress (NBS) and positive bias stress (PBS). The intact FBFETs have a subthreshold swing (SS) of 0.12 mV/dec, an on-current of ~10 -4 A, and a threshold voltage (V TH ) of -0.76 V. There is a negligible change in the on-current and SS when the FBFETs are stressed by a gate-bias voltage corresponding to an electric field of 5.4 MV/cm across the gate oxide. On the other hand, as the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Interface defects are responsible for the electrical instability of Si-based devices. Our previous simulation study has revealed that the interface traps substantially affect the electrical characteristics of FBFETs [25]. The dominant electrically-active interface defects are P b centers being dangling bonds of Si atoms that are bonded to three neighboring Si atoms in the bulk crystal; these centers are characterized by unpaired electrons localized in sp 3 -like silicon dangling bonds [24,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Interface defects are responsible for the electrical instability of Si-based devices. Our previous simulation study has revealed that the interface traps substantially affect the electrical characteristics of FBFETs [25]. The dominant electrically-active interface defects are P b centers being dangling bonds of Si atoms that are bonded to three neighboring Si atoms in the bulk crystal; these centers are characterized by unpaired electrons localized in sp 3 -like silicon dangling bonds [24,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the component diodes refresh their weights during multiplication operations. They also exhibit superior electrical stability against bias stresses (continuous input pulses), unlike other memory devices 13 , 19 – 21 , 44 , 45 . The diode array holds the binarized weight matrix semi-permanently using refresh operations while performing multiplication operations.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38,39 ] In contrast, FBFETs that operate with a positive feedback mechanism have been verified for their superior operation and environmental stability that can compete with current CMOS technologies. [ 23,40–42 ] These promising results indicate that the ternary logic gates have powerful advantages for stable and low‐power future electronics. The DG FBFET‐based ternary logic gates are desirable for data‐intensive applications such as artificial intelligence, Internet of Things, etc.…”
Section: Resultsmentioning
confidence: 99%